The 2017 regional elections in Slovakia in the aspect of the Party of the Hungarian Community (Magyar Közösség Pártja – Strana Maďarskej Komunity) - Bohár, Adam (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
In this paper I will overview how the Party of the Hungarian Community (Magyar Közösség Pártja) (MKP from now on) (SMK – Strana Maďarskej Komunity) prepared for the 2017 regional elections in Slovakia in the aspect of the party politics, in order to delegate as much candidates as possible into the regional government. The party mainly focuses on Southern Slovakia. I will also overview what kind of decisions the party made, how it reacted to the Slovakian political scene
Keywords: Slovakia; MKP; SMK; Most-Híd; Smer; SNS; regional elections; József Berényi; József Menyhárt; Nitra region; Bratislava region; Trnava region; Košice region; Banská Bystrica region